Gout: global epidemiology, risk factors, comorbidities and complications: a narrative review - Kimia Motlagh Asghari; Mahdi Zahmatyar; Fatemeh Seyedi; Alireza Motamedi; Maedeh Zolfi; Sina Janbaz Alamdary; Asra Fazlollahi; Ali Shamekh; Seyed Ehsan Mousavi; Seyed Aria Nejadghaderi; Reza Mohammadinasab; Javad Ghazi-Sha’rbaf; et al. (BMC Musculoskeletal Disorders, 2024)
Abstract Background Gout is one of the oldest known diseases and the most common form of inflammatory arthritis. The established risk factors for gout include hyperuricemia, chronic renal disease, genetic, alcohol consumption, dietary factors, diuretic use, hypertension, obesity, and metabolic syndrome. Patients with gout have an increased risk of all-cause mortality, particularly from cardiovascular disease, cancer, and infectious diseases. Gout is also associated with several complications, such as nephrolithiasis. This literature review describes the global epidemiology and trends associated with gout, before providing an overview of its risk factors and complications. Methods This research used the narrative review method. Thorough searches were performed in PubMed and Google scholar, up to June 15, 2024, for articles that evaluated the risk factors, comorbidities or complications associated with gout. Moreover, we also included studies that reported the epidemiological characteristics or burden of gout at the global, regional, or national level. Results Gout is more prevalent in developed countries, than in developing countries, although its prevalence is increasing globally. In addition, gout is much more prevalent among males than among females. Hyperuricemia has the largest role in the development of gout, although many risk factors contribute to the increasing prevalence of gout, including genes, several medications, and diet. Gout is associated with several comorbidities and complications, which need to be taken into consideration when managing gout. In recent years, gout has been found to be associated with several new comorbidities. Conclusions Our findings provide a comprehensive and informative overview that can be useful for the prevention, diagnosis, and management of gout.